Effect of Profitability, Good Corporate Governance, and Macroeconomic on Banking Stock Prices - Haekal, Achmad; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2026)
The banking subsector plays an important role in the Indonesian economy and represents the largest contributor to market capitalization on the Indonesia Stock Exchange (IDX). Stock prices can be influenced by various factors, such as financial performance, corporate governance, and macroeconomic conditions. However, empirical evidence reveals a research gap where increases in profitability are not always followed by rising stock prices, prior studies on Good Corporate Governance (GCG) show inconsistent results, and macroeconomic variables do not always align with financial theory. Moreover, studies integrating profitability, GCG, and macroeconomic factors simultaneously remain limited. This study aims to analyze the effects of financial performance, GCG, and macroeconomic factors on stock prices in the banking subsector listed on the IDX during 2020–2024. This research employs a quantitative approach using panel data regression analysis. The results indicate that Return on Equity (ROE) has a positive and significant effect on stock prices, while Net Interest Margin (NIM) and the BI Rate have a significant negative effect. Meanwhile, GCG variables and economic growth are not significant. These findings imply that investors should prioritize profitability indicators, while policymakers and management need to consider macroeconomic conditions and governance practices.